Energy availability and the female athlete triad in elite endurance athletes - Melin, A.; Tornberg, A. B.; Skouby, S.; Møller, S. S.; Sundgot-Borgen, J.; Faber, J.; Sidelmann, J. J.; Aziz, M.; Sjödin, A. (Scandinavian Journal of Medicine & Science in Sports, 2015)
The female athlete triad (Triad), links low energy availability (EA), with menstrual dysfunction (MD), and impaired bone health. The aims of this study were to examine associations between EA/MD and energy metabolism and the prevalence of Triad-associated conditions in endurance athletes. Forty women [26.2 ± 5.5 years, body mass index (BMI) 20.6 ± 2.0 kg/m2, body fat 20.0 ± 3.0%], exercising 11.4 ± 4.5 h/week, were recruited from national teams and competitive clubs. Protocol included gynecological examination; assessment of bone health; indirect respiratory calorimetry; diet and exercise measured 7 days to assess EA; eating disorder (ED) examination; blood analysis. Subjects with low/reduced EA (< 45 kcal/kg FFM/day), had lower resting metabolic rate (RMR) compared with those with optimal EA [28.4 ± 2.0 kcal/kg fat-free mass (FFM)/day vs 30.5 ± 2.2 kcal/kg FFM/day, P < 0.01], as did subjects with MD compared with eumenorrheic subjects (28.6 ± 2.4 kcal/kg FFM/day vs 30.2 ± 1.8 kcal/kg FFM/day, P < 0.05). 63% had low/reduced EA, 25% ED, 60% MD, 45% impaired bone health, and 23% had all three Triad conditions. 53% had low RMR, 25% hypercholesterolemia, and 38% hypoglycemia. Conclusively, athletes with low/reduced EA and/or MD had lowered RMR. Triad-associated conditions were common in this group of athletes, despite a normal BMI range. The high prevalence of ED, MD, and impaired bone health emphasizes the importance of prevention, early detection, and treatment of energy deficiency.